Surface air temperature trends in Kathmandu Valley for 2011-2017 - Thapa, A.; Silwal, A; Gautam, S P; Nepal, C K.; Bhattarai, S.; Timsina, D (BIBECHANA, 2021)
In this study, we reviewed the maximum and minimum temperature trends of the Kathmandu valley over the period of 2011-2017. In addition, the average monthly temperature trends were studied annually for the same period, with the data made available from the Department of Hydrology and Meteorology (DHM) of Nepal. The annual temperature trended in the same direction, with winter temperatures being lower and summer temperatures being higher. The annual average minimum and maximum air temperature trends were found to be slightly rising at 0.097˚C/year and 0.04˚C/year, respectively. The mean air temperature in Kathmandu valley is increasing at a rate of 0.06 degrees Celsius per year, with 2016 being the warmest year and 2012 being the least warm, with annual mean temperatures of 19.82˚C and 19.32˚C, respectively. The temperature difference is much smaller in the summer (less than ~12˚C) than in the winter. BIBECHANA 18 (2) (2021) 95-104